High frequency of anti-DSG 2 antibodies in post COVID-19 serum samples. (September 2022) - Lee, Edward C.Y.; Tyler, Ryan E.; Johnson, Derrick; Koh, Natalie; Ong, Biauw Chi; Foo, Shi Yin; Tan, Jack W.C.
Abstract: Background: There is growing recognition that COVID-19 does cause cardiac sequelae. The underlying mechanisms involved are still poorly understood to date. Viral infections, including COVID-19, have been hypothesized to contribute to autoimmunity, by exposing previously hidden cryptic epitopes on damaged cells to an activated immune system. Given the high incidence of cardiac involvement seen in COVID-19, our aim was to determine the frequency of anti-DSG2 antibodies in a population of post COVID-19 patients. Methods and results: 300 convalescent serum samples were obtained from a group of post COVID-19 infected patients from October 2020 to February 2021. 154 samples were drawn 6 months post-COVID-19 infection and 146 samples were drawn 9 months post COVID infection. 17 samples were obtained from the same patient at the 6- and 9- month mark. An electrochemiluminescent-based immunoassay utilizing the extracellular domain of DSG2 for antibody capture was used. The mean signal intensity of anti-DSG2 antibodies in the post COVID-19 samples was significantly higher than that of a healthy control population (19 ± 83.2 in the post-COVID-19 sample vs. 2.1 ± 7.2 ( p  < 0. 0001) in the negative control healthy population). Of note, 29.3% of the post COVID-19 infection samples demonstrated a signal higher than the 90th percentile of the control population and 8.7% were higher than the median found in ARVC patients. The signal intensity between the 6-month and 9-month samples did not differ significantly. Conclusions: We report for the first time that recovered COVID-19 patients demonstrate significantly higher and sustained levels of anti-DSG2 autoantibodies as compared to a healthy control population, comparable to that of a diagnosed ARVC group. Graphical abstract: Unlabelled Image Highlights: High levels of anti-DSG2 antibodies were found in post COVID 19 serum. The antibodies persisted long term- at least 9 months post COVID 19 infection. First demonstration of a sustained rise of specific antibody implicated in cardiac pathology in COVID 19.